Structural alterations and inflammation in the heart after multiple trauma followed by reamed versus non-reamed femoral nailing - Baur, Meike; Weber, Birte; Lackner, Ina; Gebhard, Florian; Pfeifer, Roman; Cinelli, Paolo; Halvachizadeh, Sascha; Teuben, Michel; Lipiski, Miriam; Cesarovic, Nikola; Pape, Hans-Christoph; Kalbitz, Miriam (PLoS ONE, 2020)
Background Approximately 30,000 patients with blunt cardiac trauma are recorded each year in the United States. Blunt cardiac injuries after trauma are associated with a longer hospital stay and a poor overall outcome. Organ damage after trauma is linked to increased systemic release of pro-inflammatory cytokines and damage-associated molecular patterns. However, the interplay between polytrauma and local cardiac injury is unclear. Additionally, the impact of surgical intervention on this process is currently unknown. This study aimed to determine local cardiac immunological and structural alterations after multiple trauma. Furthermore, the impact of the chosen fracture stabilization strategy (reamed versus non-reamed femoral nailing) on cardiac alterations was studied. Experimental approach 15 male pigs were either exposed to multiple trauma (blunt chest trauma, laparotomy, liver laceration, femur fracture and haemorrhagic shock) or sham conditions. Blood samples as well as cardiac tissue were analysed 4 h and 6 h after trauma. Additionally, murine HL-1 cells were exposed to a defined polytrauma-cocktail, mimicking the pro-inflammatory conditions after multiple trauma in vitro. Results After multiple trauma, cardiac structural changes were observed in the left ventricle. More specifically, alterations in the alpha-actinin and desmin protein expression were found. Cardiac structural alterations were accompanied by enhanced local nitrosative stress, increased local inflammation and elevated systemic levels of the high-mobility group box 1 protein. Furthermore, cardiac alterations were observed predominantly in pigs that were treated by non-reamed intramedullary reaming. The polytrauma-cocktail impaired the viability of HL-1 cells in vitro, which was accompanied by a release of troponin I and HFABP. Discussion Multiple trauma induced cardiac structural alterations in vivo, which might contribute to the development of early myocardial damage (EMD). This study also revealed that reamed femoral nailing (reamed) is associated with more prominent immunological cardiac alterations compared to nailing without reaming (non-reamed). This suggests that the choice of the initial fracture treatment strategy might be crucial for the overall outcome as well as for any post-traumatic cardiac consequences.
CRIS-Team Scopus Importer:2020-12-21